Pengaruh Pembangunan Ekonomi Islam dengan Kesejahteraan Masyarakat Islam di Indonesia - Aina Aulia, Nurul; Widyaningtias, Rizka; Syifa Rahmania, Dwiana (Universitas Pembangunan Nasional Veteran Jakarta, 2024)
Abstract The development of sharia economics in Indonesia is expected to have a positive impact on the welfare of the Islamic community. Several factors that can influence the welfare of Islamic communities in Indonesia include the implementation of sharia economics, the role of Islamic charity and philanthropic institutions, social conditions and poverty, and the Islamic economic system. The implementation of sharia is expected to provide prosperity for society, while Islamic charitable and philanthropic institutions play a role in improving the economic welfare of society by carrying out good deeds for the public interest. However, there are still challenges in overcoming poverty levels and achieving equal distribution of prosperity for the entire community. Therefore, greater efforts are needed to improve the welfare of Muslims in Indonesia, both in the economic, social and justice fields. The development of sharia economics is expected to have a positive impact on the welfare of the Islamic community in Indonesia by providing a sense of justice, togetherness, kinship and being able to provide opportunities for everyone. Keywords: Islamic Economics; Prosperity; Challenges Abstrak Pembangunan ekonomi Islam di Indonesia diharapkan dapat memberikan dampak positif pada kesejahteraan masyarakat Islam. Beberapa faktor yang dapat mempengaruhi kesejahteraan masyarakat Islam di Indonesia meliputi penerapan ekonomi syariah, peran lembaga amal dan filantropi Islam, kondisi sosial dan kemiskinan, serta sistem ekonomi Islam. Penerapan ekonomi syariah diharapkan dapat memberikan kesejahteraan bagi masyarakat, sedangkan lembaga amal dan filantropi Islam berperan dalam meningkatkan kesejahteraan masyarakat dengan melakukan perbuatan baik untuk kepentingan umum. Namun, masih terdapat tantangan dalam mengatasi tingkat kemiskinan dan mencapai kesejahteraan yang merata bagi seluruh masyarakat. Oleh karena itu, diperlukan upaya yang lebih besar untuk meningkatkan kesejahteraan masyarakat Islam di Indonesia, baik dari segi ekonomi, sosial, maupun keadilan. Pembangunan ekonomi Islam diharapkan dapat memberikan dampak positif pada kesejahteraan masyarakat Islam di Indonesia dengan memberikan rasa keadilan, kebersamaan, kekeluargaan serta mampu memberikan kesempatan bagi siapapun. Kata Kunci: Ekonomi Islam; Kesejahteraan; Tantangan